PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT DAN PUPUK N, P DAN K TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays. L Var saccarata Sturt) - Haryawan, Budi; Sofjan, Jurnawaty; Yetti, Husna (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Sweet corn (Zea mays L. varsaccarata Sturt) is a plant that is harvested young and many of them cultivated in tropical regions in Indonesia. This study aims to determine the effect of interaction TKKS compost and fertilizer N, P, and K on the growth and yield of sweet corn, as well as getting the best dose. Experiments conducted at the Faculty of Agriculture, University of Riau, Pekanbaru in April and July 2014. The study was conducted experiments using a factorial randomized block design (RCBD), 3 replications. Factor 1: Compost TKKS and Factor 2: Fertilizer N, P and K (Urea, SP-36 and KCl). Parameters those measured were plant height (cm), stalk diameter (mm),  tasseling time  (DAP), silking time (DAP), harvesting time (DAP), cob diameter (mm), husked cob weight / 4, 5 m2 (kg) and without husk cob weight / plot. The results showed those compost TKKS with Urea, SP-36 and KCl observations showed interaction parameter appears when the tassel and silking time, a single factor in the treatment of compost TKKS significantly different at a time parameter tasseling time and husked cob weight while single factor Urea, SP-36 and KCl had no meaning on all parameters. Fertilizer combination TKKS 4 ton / ha with urea (225 kg / ha), SP-36 (150 kg / ha) and KCl (75 kg / ha) gives a high weight of husked cobs with the acquisition of the results of 9.167 kg / 4.5 m2, equivalent to 20.373 tons / ha, compared with those without compost TKKS and without Urea, SP-36 and KCl husked cob weight gain of 7.133 kg / 4.5 m2, equivalent to 15.839 tons / ha (up 22.25%).   Keywords: Sweet corn, compost and fertilizer NPK TKKS